SMARTPHONE ADDICTION AND SLEEP QUALITY AMONG STUDENTS - Nikolic, Aleksandra; Grujicic, Sandra (Medicinski podmladak, 2023)
Abstract The use of smartphones and accompanying apps has significantly improved communication, but it has also raised concerns about device dependence and overuse. The term "smartphone addiction" was introduced to describe the excessive and dysfunctional use of smartphones, evocative of behavioral addictions. Since smartphones are used for various purposes and are always connected to the Internet, they can significantly affect daily activities. Excessive and problematic smartphone use is associated with poor sleep, fatigue, difficulty falling asleep, and shorter sleep duration. It has been demonstrated that the addictive use of smartphones is commonly accompanied by depression, anxiety, and stress. Additionally, the lack of sleep is strongly associated with academic underperformance. Therefore, maintaining healthy sleep patterns is essential for young people and improves their academic performance as well as physical and mental health. As smartphone addiction becomes a growing challenge in many countries, preventive measures need to be implemented, as well as measures to help reduce the consequences of excessive smartphone use.